## Math-Linux.com

Knowledge base dedicated to Linux and applied mathematics.

Home > Mathematics > Derivative of a function > Derivative of inverse functions

# Derivative of inverse functions

Derivative of the inverse function f^-1 is given by : (f^-1)’(x)=1 / f’ (f^-1(x))
To prove this result, we are going to apply the Chain rule (derivative of a composite function) to the function f and to its inverse f^-1.

## Mathematical Reminder

We previously demonstrated the result relating to the Chain Rule.

Consider $I$ and $J$ two intervals of $\mathbb{R}$ and two functions $u, v$ defined by

\begin{aligned} u&: I \rightarrow \mathbb{R}\\ v&: J \rightarrow \mathbb{R} \end{aligned}

such $f(I) \subset J$. Let $x$ a point of the interval $I$.
If $u$ is differentiable at $x$ and $v$ is differentiable at $u(x)$ then the composite function $u \circ v$ is differentiable at $x$, and the Chaine Rule is given by

$$\forall x\in I, \quad \left(u \circ v\right)^{\prime}(x)=u^{\prime}(v(x)) \cdot v^{\prime}(x)$$

## Proof/Demonstration

By applying the Chain Rule derivative of composite function avec $u=f,v=f^{-1}$, we have:

$$\left(f \circ f^{-1}\right)^{\prime}(x)=f^{\prime}(f^{-1}(x)) \cdot (f^{-1})^{\prime}(x)$$

However, by definition of a reciprocal function:

$$\left(f \circ f^{-1}\right)(x)=\left(f^{-1} \circ f\right)(x)=Id(x)=x$$

where $Id$ is the identity function.

Then:

$$\left(f \circ f^{-1}\right)^{\prime}(x)=\left(Id\right)^{\prime}(x)=1$$

Thus

\begin{aligned} \left(f \circ f^{-1}\right)^{\prime}(x)&=f^{\prime}(f^{-1}(x)) \cdot (f^{-1})^{\prime}(x)\\ &=1 \end{aligned}

We conclude:

$$(f^{-1})^{\prime}(x)=\frac{1}{f^{\prime}(f^{-1}(x))}$$